Quantification of C-reactive protein, differential count and blood glucose in acute coronary syndrome - Padmanaban, U. B.; ., Lenin; Kumar, G. Sathish (International Journal of Advances in Medicine, 2020)
Background: The study was done to investigate whether the raised levels of C-reactive protein (CRP), differential count and random blood glucose, besides echocardiogram, enhances the assessment process of acute coronary syndrome (ACS). Methods: This prospective study was done on 100 patients with typical chest pain attending to the department of medicine at K.A.P.V Medical College and Hospital, Trichy during the period from 2015 to 2017. The serum was assayed on admission for CRP, differential count and random blood glucose. Correlation of these parameters with incidence of ACS was calculated. Results: Male preponderance was seen in the study. Out of 100 patients, majority of about 60% of ACS patients had raised JVP. Elevated level of CRP was seen in 73% patients, 70% had elevated level of ejection fraction percentage. 71% had elevated level of WBC and 58% had elevated level of RBS. Statistically significant correlation was observed with the level of CRP (p=0.044), differential WBC count (p=0.037) and random blood glucose levels (p=0.001). Conclusions: Our study indicates that elevated CRP levels, increased random blood sugars and leucocytosis in ACS patient are positively correlated with decreased ejection fraction. Hence, measuring the levels of these parameters will helps in identifying incidence of acute coronary syndrome without echocardiogram.